Asymmetries in single and triple hop are not detrimental to change of direction speed - dos Santos, T.; Thomas, C.; Jones, P. A.; Comfort, P. (Journal of Trainology, 2017)
Objectives: To determine the impact of between limb asymmetries in hop performance on change of direction speed (CODS). Design and Methods: Twenty-two multisport collegiate athletes (mean ± SD; age: 21.8 ± 3.4 years, height: 178.1 ± 6.7 cm, mass: 73.5 ± 7.1kg) performed three single and triple horizontal hops for distance per limb, followed by three modified 505 and 90°cut CODS trials each side to establish imbalances between right and left, and dominant (D) and non-dominant (ND) limbs. Limb dominance was defined as the limb that produced the furthest hop or faster CODS performance. Results: Paired sample t-tests revealed no significant differences in hop performance and CODS performance between right and left limbs (p > 0.05, g = 0.11), however, significant differences were observed when comparing D and ND limbs (p < 0.001, g = 0.46-0.61). No significant correlations were observed between hop imbalance and CODS performance (p > 0.05, r = 0.35). Low agreements (32-55%) were demonstrated between like for like identifications of asymmetry for CODS and hop performance. Conclusions: Imbalances in hop and CODS were present; however, greater hop imbalances were not detrimental to CODS. Furthermore, the D limb for hopping did not necessarily correspond to faster performance from that limb during 180° turns and 90° cuts (plant foot). Collegiate male multi-sport athletes with imbalances within the range reported within this study (= 15%) should not experience associated CODS detriments.